Role of protein kinase CK2 in the dynamic interaction of platelets, leukocytes and endothelial cells during thrombus formation. Issue 5 (November 2015) - Ampofo, Emmanuel; Müller, Isabelle; Dahmke, Indra N.; Eichler, Hermann; Montenarh, Mathias; Menger, Michael D.; Laschke, Matthias W.
Abstract: Introduction: Thrombus formation is a complex process, which is characterized by the dynamic interaction of platelets, leukocytes and endothelial cells. The activation of these cells is strictly mediated by different phospho-regulated signaling pathways. Recently, it has been reported that inhibition of protein kinase CK2 affects platelet function by suppressing phosphatidylinositol-4, 5-bisphosphate-3-kinase (PI3K) signaling. Based on this finding, we herein analyzed whether CK2 acts as a crucial regulator of thrombus formation. Materials and methods: We examined the effect of CK2 inhibition on platelet activation and aggregation, the formation of platelet-leukocyte aggregates (PLA), the endothelial expression of von Willebrand factor (vWF), intercellular adhesion molecule (ICAM)-1 and vascular cell adhesion molecule (VCAM)-1, and the subcellular localization of nuclear factor of activated T-cells cytoplasmic 1 (NFATc1) and phospho-p65 in human dermal microvascular endothelial cells (HDMEC). Dorsal skinfold chambers were prepared in BALB/c mice to analyze in vivo the effect of CK2 inhibition on photochemically induced thrombus formation using intravital fluorescence microscopy. Results: CK2 inhibition by CX-4945 suppressed adenosin diphosphate (ADP)- and proteinase-activated receptor-1-peptide (PAR-1-AP)-stimulated platelet aggregation, which was associated with down-regulation of P-selectin, GPIIb/IIIa and a reduced formation of PLA. Expression and secretion of vWF was diminished in CX-4945-treated HDMEC. Moreover, CK2 inhibition attenuated the endothelial expression of VCAM-1, whereas the expression of ICAM-1 was not affected. Finally, CX-4945-treated mice exhibited a significantly delayed photochemically induced thrombus formation when compared to vehicle-treated controls. Conclusion: These results indicate that CK2 is a pleiotropic regulator of thrombus formation, affecting multiple interactions of platelets, leukocytes and endothelial cells. Highlights: The CK2 inhibitor CX-4945 suppresses platelet activation and aggregation. CX-4945 inhibits the formation of platelet-leukocyte aggregates (PLA). CX-4945 reduces the endothelial expression of vWF and VCAM-1. CX-4945 delays photochemically induced thrombus formation.